(3QSGdI aj MQa dhs - (3GdMGL Ndjd CafOjs
(3ChdgG (B:s
(3MeOG hUdGI hSdGeG hHYO(B: (3bO dGM dfG HYO GSJbQGA RHQ GdegQI hGSJeGY cdGe Gdced Cf aj (B((3dh(B) (3NeSI ChLg(B: (3CMOgG(B: (3Cf Jchf MQa EdG CfgG dG JLRe cbhdc dh LFJfj dCcQeJc eYdbG GdEcQGe HGdeLjA hajg CQHY ebGdGJs
(3BNQgG (B:s
(3EPG cGf GdTQW eeG jSJHYO GSJdRGeg dPdc GdLRGA hjchf fbjV Pdc CfSH hCdjb HGSJdRGeg dPdc GdLRGA cebGdI GdbGSejI fYe YHO UgjH (B((3cPG(B) (3dh de jNa Gddg de jYUg hcebGdJc dh CgfJfj dCJjJ Ydjc jYfj Cf YOe GdYUjGf KGHJ dUgjH aj LejY GdCRefI ShGA NGa Ch de jNa JCeds
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdHdGZIs